Modeling desorption isotherms and thermodynamic properties of Italia grapes. Issue 10 (13th July 2020) - Khiari, Ramla; Zemni, Hassène; Maury, Chantal; Mihoubi, Daoued
Abstract: The purpose of this work was to establish the desorption isotherms and thermodynamic characteristics of grapes cv. Italia. These characteristics are important tools in food science, particularly due to their contribution to the prevision of quality, constancy, and durability of agri‐food commodities. Desorption isotherms were determined by the static gravimetric method. All the curves revealed type II behavior, according to Brunauer's classification. The desorption isotherms fitted by eight equations showed that Adam and Shove and also the GAB models gave the best fit to the experimental results. But the GAB model was recommended for the prediction of the desorption isotherms of Italia grapes owing to its physical explanation of the sorption process compared to the Adam and Shove model which was purely empirical. The moisture isotherms were exothermic, enthalpy driven, and spontaneous. The enthalpy–entropy compensation existed with an isokinetic temperature of 390 K. Practical applications: The stability of dehydrated grapes is influenced by its water activity and hygroscopic properties. Desorption isotherms are essential tools in drying processes for the selection of the proper operating conditions of drying, packaging, and storage requirements for the desired product shelf life. Thermodynamics properties have been reported as one of the approaches used to understand the water properties in the food matrix and calculate the energy requirements of heat and mass transfer in food drying.